Fate of nanoparticles in the central nervous system after intrathecal injection in healthy mice - Householder, K. T. (Sci Rep, 2019)
Cerebrospinal fluid (CSF) is produced in the cerebral ventricles and circulates within the subarachnoid space (SAS) of the brain and spinal cord, where it exchanges with interstitial fluid of the parenchyma. The access of CSF to the entire central nervous system (CNS) makes it an attractive medium for drug delivery. However, few intrathecal (IT) therapies have reached the clinic due, in part, to limited distribution and rapid clearance. Given the success of nanoparticle (NP) carriers in prolonging circulation and improving delivery of systemically administered agents, we sought to evaluate the distribution of IT injected NPs within the CNS. We administered fluorescent, 100 nm PEGylated-NPs into the cisterna magna of healthy mice and studied their distribution along the brain and spinal cord. Our data demonstrate that NPs are capable of distributing rapidly through the SAS along the entire neuraxis with reproducible, anatomically defined patterns of delivery. NPs were well retained within the leptomeninges for over 3 weeks, showing preference for ventral surfaces and minimal penetration into the CNS parenchyma. Clearance of NPs occurred across the cribriform plate into the nasal mucosa, with a small fraction of NPs localizing with nerve roots exiting the spinal column. Larger 10 µm particles were also capable of moving through the SAS but did not achieve as widespread distribution. These studies demonstrate the ability of NPs to achieve widespread delivery along the neuraxis and highlight IT administration as a potentially significant route of administration for delivery of nanomedicine to the subarachnoid space.